(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This thesis explores the cultural, linguistic, and social significance of proverbs and idioms in English-speaking communities. Proverbs and idioms, as essential components of language, reflect cultural heritage, societal values, and shared wisdom. By analyzing their origins, linguistic features, and usage in literature and media, this study highlights how these expressions shape communication, foster cultural identity, and preserve historical traditions. The research also examines the role of proverbs and idioms in language learning and translation, revealing their complexities and universal appeal.